Implementation of The Effectiveness of Regional Autonomy in Indonesia - Aminah, Aminah; Gantyowati, Evi; Winarna, Jaka; khairudin, khairudin; Redaputri, Appin Purisky (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
The drive of this study is to postulate empirical evidence about the evaluation of the enactment of regional autonomy in Indonesia after the enactment of Act Number 22 Year 1999 concerning Regional Government. Exclusively, this analysis aims to evaluate the wellbeing of the community, public services and regional competitiveness in the new autonomous regions. This research was conducted in 71 new autonomous regions in the Sumatra region after the depiction of Act Number 22 of 1999 concerning Regional Government during the 2000-2018 period.Ã‚Â  This type of research uses quantitative research. While the research method used is descriptive method, which is a research method that describes the population under study and consists of variables. The results of the study found that (1) the success rate of implementing regional autonomy for 20 years in the Sumatra region from the welfare aspect was 64.78%, meaning that the implementation of regional autonomy in the Sumatra region so far (64.78%) "has succeeded in increasing the HDI" according to the mandate of the law; (2) the level of success in implementing regional autonomy for 20 years in the Sumatra region from the aspect of regional competitiveness is 18.30%. The conclusion is that the implementation of regional autonomy in the Sumatra region has not been sufficiently successful in increasing regional competitiveness in terms of GRDP; (3) Riau Province is a region that has been very successful in implementing regional autonomy both in terms of welfare and regional competitiveness.